Statistical Yearbook 2007, Fifty-second Issue - United Nations Department of Economic; Social Affairs (United Nations, 2013)
The United Nations Statistical Yearbook is an annual compilation of a wide range of international economic, social and environmental statistics for over 200 countries and areas, compiled from sources including UN agencies and other international, national and specialized organizations. The fifty-second issue contains data available to the Statistics Division as of June 2008 and presents them in 68 tables on topics such as: agriculture; balance of payments; communication; development assistance; education; energy; environment; finance; gender; industrial production; international merchandise trade; international tourism; labour force; manufacturing; national accounts; nutrition; population; prices; research and development; and wages. The number of years of data shown in the tables varies from one to ten, with the ten-year tables covering 1996 to 2005 or 1997 to 2006. Accompanying the tables are brief descriptions of major statistical concepts.